A Modified Vilsmeier–Haack Strategy to Construct β-Pyridine-Fused 5,10,15,20-Tetraarylporphyrins - Pargat Singh (SynOpen, 2020)
Abstract A modified Vilsmeier–Haack strategy has been developed to construct a novel series of π-extended nickel(II) or copper(II) complexes of 2-chloro-3-formyl- and 3-formylpyrido[2,3-b]porphyrins from 2-acetamido-meso-tetraarylporphyrins. After chromatographic purification and spectral characterization, nickel(II) complexes of 2-chloro-3-formyl- and 3-formylpyrido[2,3-b]porphyrins underwent reaction with malononitrile under Knoevenagel conditions to afford new porphyrins with extended π-conjugation in appreciable yields. On photophysical investigation, the newly prepared pyridoporphyrins displayed a significant redshift in their electronic absorption spectra as compared to simple meso-tetraarylporphyrin precursors.